Winning Beats Learning: Environmental education in Indonesian senior high schools. Issue 136 (2nd September 2018) - Prabawa-Sear, Kelsie
ABSTRACT: This article examines approaches to environmental education (EE) in schools in Yogyakarta and Surabaya, Indonesia. To make sense of a situation where the education part of environmental education is almost non-existent, it draws on ethnographic data to demonstrate how Indonesian EE fits within the broader education system. The data show how much of EE is competitive, such that there is a focus on winning over environmental learning.